The Influence of DER, RTO, CR, TATO, And EPS on Stock Prices in Wholesale Sub Sector Companies - Eldwin Wiliem; Gregorius Widiyanto (eCo-Buss, 2022)
This study analyzes the impact of DER, RTO, CR, TATO, and EPS on share prices of companies in the wholesale sub-sector listed on IDX in the 2016-2020 period. The object of this research are companies that are members of the wholesale sub-sector. The method used is a quantitative method with literature review and documentation techniques. The total number of companies are 47 companies, so there are 12 companies that meet the criteria made by the author. In this study using several analytical techniques in the form of classical assumption test, multiple linear regression test, multiple correlation test and hypothesis testing namely ttest and Ftest. The results of data analysis prove